The Role of Family Counseling to Improve Communication and Harmony in the Family - Afifah; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
Family counseling is an effort to help people through the process of interpersonal interaction between counselors and clients so that clients can make decisions, set goals and understand themselves and their environment in order to feel happy and be able to control their behavior effectively. The research method used is the library method, where information is collected from various literature sources such as books, scientific reports, and journal articles. Library research is used to collect relevant information from various sources to support the role of family counseling to improve communication and harmony in the family. The results of the study indicate that family counseling is an effort to help family members understand and resolve their internal dynamics. The objectives of this counseling include developing balance and harmony between family members, as well as improving communication and relationships within the family. Communication in the family is emphasized as an important foundation for maintaining healthy and harmonious relationships. Effective communication in the family includes the ability to respect each other, be clear in conveying messages, be empathetic, and humble. A harmonious family is characterized by a commitment to support and care for each other, provide enjoyable time together and incorporate principles, morals and spirituality into everyday life.